﻿The uniformity of broadcast media in the muslim world during the age of globalization - Zulkifle Abd Ghani (Penerbit Universiti Kebangsaan Malaysia, 2011)

(untitled)
﻿Muslim culture is ideally derived from the culture of knowledge and communication. As understood from the notion of 'ilm (knowledge) and iqra '(read). the history of communication in lslam has been firmly based on the transmission of al-din (religion) as a comprehensive way of life. Knowledge has been transmitted to the Muslim society through oral communication, written materials as well as printing and broadcast media. However the development of both printing and broadcast media was attributed directly or indirectly to colonialism or Western dominance. In the colonial and post- colonial Muslim world, the media were said to be slowly incorporated into an international secular culture. Today in the globalized world. the uniformity of broadcast media. in the Muslim world is in a need to be re-examined. This paper will evaluate how far the broadcast media in the Muslim world has been consructed based on philosophy and goals that are tied to the concept of al-din. Furthermore, the paper will also discuss the impacts of globalization to the contents of the media. lt is argued that globalization has "imposed" some sorts of the new challenges to the Muslim world. especially with regards to the media philosophy, structure and technology.